TRADISI “AMBRUK” MASYARAKAT DUSUN NGESONG DALAM PERSPEKTIF HUKUM ISLAM - Guntur, Ahmad Zamzam (IAIN Kediri, 2015)
This article discusses the phenomenon of ambruk tradition in Ngesong, Tiron village, Banyakan-Kediri. Ngesong community has a tradition in which candidate of bridegroom and bride which have not been legal based on Islamic law and State law stay in one house. Through sociology approach, this article tries to investigate this socio-culture context. Ambruk tradition is a tradition done after engagement session and the decision of the marriage day by transferring the candidate of bridegroom to the family of the candidate of the bride. Ambruk tradition has two aspects namely helping works of the candidate of the parent in-law and staying in the parent in-law’s house. In Islamic law perspective, ambruk tradition is prohibited; though helping the candidate of the parent in-law is permitted. Staying in the candidate of parent in law’s house although for helping them is ‘urf fasid since it is harmful and makes sin of khalwah and zina. Meanwhile, the afraid of making damage or sins must be prohibited. Therefore, based on sadd al-dhari’ah concept, ambruk tradition cannot be permitted.Keywords; Tradisi ambruk,pinangan, sadd al-dhari’ah,‘urf fāsid